To the Productive Space Circuit and Circuits of the Urban Economy: a link between the retail trade of apparel from União dos Palmares-AL and Polo de Confecções de Pernambuco / Ao Circuito Espacial Produtivo e Circuitos da Economia Urbana: elo entre o comércio varejista de vestuário de União dos Palmares-AL e o Polo de Confecções de Pernambuco - Cristiane da Silva (Universidade Estadual de Alagoas, 2019)
The paper seeks to understand the dynamics of the economy of the Palmares-AL Union, based on the interpretation of the theory of the two circuits of the urban economy (2008, [1979]) and the performance of space production circuits in the characterization of stages in the garment industry. It is proposed to analyze the lower circuit of the clothing retail sector in the city of União dos Palmares and its relation with the lower and upper marginal circuit of the Polo de Confecções de Pernambuco, constituted by the triangle of the cities of Caruaru - PE, Santa Cruz do Capibaribe - PE and Toritama - PE. We understand that the lower circuit is formed by the set of small activities that meets the needs of the poor population, in the cities. The upper marginal circuit corresponds to the survival of activities that do not interest the agents who command the economy or the emergence of activities that fill the vacancies left by recent modernizations. In order to understand the dynamics of the activities of the circuits, they are considered, characteristics the organization of the activities. The analysis of the lower circuit from the performance of micro and small companies, however it is understood that this characterization gives us only a partial apprehension, since it encompasses several activities from the peddler to the small establishment. It is considered other elements in the investigation, which show the directions of consumption and the persistence of poverty and the insertion of new variables attributed to the process of modernization in the lower circuit. However, we understand that the modernization is selective, occurs at different levels in the same city, in the center and in its periphery.